A case report on choledochotomy with t-tube in rare case of oriental cholangiohepatitis in 33-year-old male patient - Kavad, Harshad M.; Patel, Hardik; Patel, Tejas; Astik, Hardik (International Surgery Journal, 2024)
A 33-year-old male patient presented in OPD with c/o abdominal pain in right hypochondrium since 1 month which is mild in nature and intermittent on and off type and yellowish sclera since 1 year which is gradually increases. On CECT abdomen shows CHD dilated (15 mm) and sludge within it, RHD dilated (15 mm) and sludge within it, LHD dilated (11 mm) and calculus within it. patient is operated with choledocotomy with T-tube insertion in CBD, post operatively patient had significant improvement in clinical symptoms and lab findings also suggestive of better outcome.